Psychological barriers involved in applying for a job: Does metastereotyping negatively impact the employability beliefs of women in business - Chua, Vance Justin C. (Animo Repository, 2023)
In terms of employability beliefs, the researchers will focus on the meta stereotypes that women have about businesses. The study’s purpose is to establish whether meta stereotyping has an impact on the employability beliefs of women, as well as the effects of gender stereotypes and how they may affect women's career progress. The study will be using a quantitative research design with causal and descriptive approach. The data was collected through an online survey questionnaire through the use of purposive sampling, garnering a total of 205 responses. Using simple linear regression, multiple linear regression, mediation analysis, and moderation analysis; results show that there is a significant relationship between meta stereotype negativity and employability beliefs, state self-esteem and employability belief, and meta stereotype negativity and state self-esteem. Additionally, state self-esteem has a mediating effect on the relationship between meta stereotype negativity and employability beliefs. However, dispositional self-esteem does not moderate the relationship between state self-esteem and the employability beliefs. Implications from the results show that stigmatizations against women in the business world should be eliminated, initiatives for diversity and inclusion should be implemented so that women in business will retain a positive state self-esteem.